Research Trends of Stunting Related to Insulin-Like Growth Factor-1: Bibliometric Analysis - Lukman Hardia; Agus Sangka Pratama; A. M. Muslihin (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is a condition in which a person's height is less than normal based on age and gender. The prevalence of stunting in Indonesia in 2021 is 24.4%. This illustrates that stunting is still a problem that cannot be resolved in Indonesia. Research on the incidence of stunting was carried out to determine its relationship with insulin-like growth factor-1 (IGF-1) levels. Search results on the Pubmed database obtained 446 English-language articles published from 1993 – April 12, 2023. The results of bibliometric analysis and VOSViewer show that new research trends began to be seen in 2018 to 2023 even though there had been publications previously in 1993 and 2000, but very minimal amount. The most dominating document types were journal articles with 310 publications (69.51%) and reviews with 89 publications (19.96%). The most trending keywords are humans (268), female (176), male (145), animals (142), insulin-like growth factor i/metabolism (94), child (74), adult (60), mice (56), pregnancy (47) and child preschool (43). The publishing journals that published the most articles were Frontiers in Endochronolgy (22 publications), International Journal of Molecular Sciences (19 publications), Scientific Reports (13 publications). The highest number of author collaborations is from the USA with 78 articles being the country with the most collaboration on both SCP and MCP with an MCP to SCP ratio of 0.244. China ranks second with the number of articles of 63 with an MCP ratio of 0.190.